2010
DOI: 10.1086/654817
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Nef Induces Dyslipidemia in Simian Immunodeficiency Virus–Infected Macaques by Suppressing Cholesterol Efflux

Abstract: HIV infection and subsequent antiretroviral therapy have been associated with an increased incidence of dyslipidemia and cardiovascular disease and has been shown to suppress cholesterol efflux from virus-infected macrophages by inducing Nef-dependent downregulation of ABCA1. The SIV/macaque model was used to examine consequences and mechanisms involved. SIV infection drove a significant remodeling of high-density lipoprotein profiles suggesting systemic inhibition of the ABCA1-dependent reverse cholesterol tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
60
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
3

Relationship

5
5

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 51 publications
5
60
0
Order By: Relevance
“…HIV, via the viral accessory protein Nef, inhibits activity of the ATP binding cassette transporter A1 (ABCA1), an integral transmembrane lipid transporter ( 4 ), and impairs cholesterol effl ux from macrophages, causing accumulation of cholesterol in these cells and their transformation into foam cells, a hallmark of atherosclerosis ( 3 ). Furthermore, extracellular Nef secreted by HIV-infected cells can inhibit cholesterol efflux from uninfected cells and cause impairment of systemic reverse cholesterol transport ( 5 ). On the other hand, stimulation of cholesterol effl ux through activation of ABCA1 suppresses HIV-1 infection ( 6 ).…”
Section: Lipid Raft Cholesterol Content Analysismentioning
confidence: 99%
“…HIV, via the viral accessory protein Nef, inhibits activity of the ATP binding cassette transporter A1 (ABCA1), an integral transmembrane lipid transporter ( 4 ), and impairs cholesterol effl ux from macrophages, causing accumulation of cholesterol in these cells and their transformation into foam cells, a hallmark of atherosclerosis ( 3 ). Furthermore, extracellular Nef secreted by HIV-infected cells can inhibit cholesterol efflux from uninfected cells and cause impairment of systemic reverse cholesterol transport ( 5 ). On the other hand, stimulation of cholesterol effl ux through activation of ABCA1 suppresses HIV-1 infection ( 6 ).…”
Section: Lipid Raft Cholesterol Content Analysismentioning
confidence: 99%
“…HIV-1 infection is associated with a high risk of developing atherosclerosis (1), and studies in animal models and in vitro demonstrated that Nef-mediated impairment of ATP-binding cassette transporter A1 (ABCA1) 3 function may contribute to this side effect of HIV infection (2)(3)(4). ABCA1 mediates transport of cholesterol and phospholipids to lipid-poor apolipoprotein A-I (apoA-I), which is the initial step in the process of reverse cholesterol transport and HDL formation (5).…”
mentioning
confidence: 99%
“…In these cases, viral infection is observed in epithelial cells and can be associated with marked cytomegaly and the presence of intranuclear inclusion bodies, which vary in size and characteristics based on adenovirus genotype (Figs. [1][2][3][4]. A mixed inflammatory cell infiltrate that can be primarily mononuclear or neutrophilic may be observed, although in cases of severe immunodeficiency, the inflammatory reaction may be minimal.…”
Section: Adenoviridaementioning
confidence: 99%